Applying multicriteria decision analysis to design safe road projects - Sarrazin, Renaud; Smet, Yves de (European Journal of Transport and Infrastructure Research, 2015)
Over the past decade, the improvement of road safety had been a major issue in transport strategies in Europe. Simultaneously the concept of sustainable development has become a key element in many strategic and operational policies – including the road sector ones. However, considering the design stage of road infrastructure, there are almost no methodologies that both quantify the road safety performance of the project and consider its economic and environmental nature. This study seeks to develop a preventive evaluation model based on a multicriteria decision analysis. It would allow designers to assess the safety performance and to evaluate some of the economic and environmental impacts of their road projects at the design stage. For this purpose, we have defined a set of 13 criteria which describe the problem. The aim of this paper is to highlight the added value and limits of such an approach. A case study is analysed in order to quantify these arguments. In particular, we apply the PROMETHEE-GAIA method to our problem and we conduct a sensitivity analysis to prove the interest of using a multicriteria decision technique in the context of road designing. A brief presentation of the current and future developments introduces the notion of Pareto frontier and its characterization with a genetic algorithm. Finally, the conclusion and discussion point out the possibilities and impossibilities of this research.